Feeding rumen-protected gamma-aminobutyric acid enhances the immune response and antioxidant status of heat-stressed lactating dairy cows. (August 2016) - Cheng, Jianbo; Zheng, Nan; Sun, Xianzhi; Li, Songli; Wang, Jiaqi; Zhang, Yangdong
Abstract: This experiment was conducted to investigate the effects of rumen-protected gamma-aminobutyric acid (GABA) on immune function and antioxidant status in heat-stressed dairy cows. Sixty Holstein dairy cows were randomly assigned to 1 of 4 treatments according to a completely randomized block design. The treatments consisted of 0 (control), 40, 80, or 120 mg of GABA/kg DM from rumen-protected GABA. The trial lasted 10 weeks. The average temperature-humidity indices at 0700, 1400 and 2200 h were 78.4, 80.2 and 78.7, respectively. Rectal temperatures decreased linearly at 0700, 1400, and 2200 h with increasing GABA. As the GABA increased, the immunoglobulin (Ig) A and IgG contents and the proportions of CD4 + and CD8 + T lymphocytes increased linearly ( P <0.05), whereas concentrations of interleukin (IL)-2, IL-4, IL-6 and tumor necrosis factor-α (TNF-α) decreased linearly ( P <0.05). The activities of superoxide dismutase (SOD), glutathione-peroxidase (GSH-PX) and total antioxidant capacity (T-AOC) increased linearly ( P <0.05), whereas malondialdehyde (MDA) content decreased linearly ( P <0.05) with increasing GABA. These results indicate that rumen-protected GABA supplementation to heat-stressed dairy cows can improve their immune function and antioxidant activity. Highlights: We develop a new strategy that can help maintain heat-stressed dairy cows' health. Gamma-aminobutyric acid (GABA) was supplemented to heat-stressed dairy cows. Rumen-protected GABA can improve immune function in heat-stressed dairy cows. Rumen-protected GABA can improve antioxidant activity in heat-stressed dairy cows.